Tata ruang dalam rumah sederhana tipe 54 perumahan Kedung Badak Baru Bogor ditinjau dari pencahayaan (ARTEKS : Jurnal Teknik Arsitektur, 2018)
Indonesian people considered the house as a basic necessity such as a house with a building area of 54 m2. The placement of the various layout to the sun’s orientation is related to the lightning. This led to the phenomenon of affordable housing development. The issue of this research is the layout of type 54 affordable house considered by the lighting. The focus of this research is the type 54 affordable house in Kedung Badak Baru in Bogor. The purpose of this research is to get layout design guidelines of type 54 affordable house which consider the lighting and give input to the next architect and government in Bogor. The research method is quantitative descriptive analytic. Tropical architecture design theory and lighting theory are used as a reference in making an analysis. The result is the interior less bright. It because the layout design was surrounded by another room and incorrect placement and size of openings. The conclusion is to design new layout based each orientation of type 54 affordable house. And it also to place the suitable openings properly which will able to utilize the light.
Keywords: affordable house type 54; layout; lighting